The adoption of global water norms in Central America: What separates normative coherence from normative hegemony?. (22nd March 2022) - Kauffer, Edith; Maganda, Carmen
Summary: Motivation: Water management is currently sustained by international norms negotiated in global meetings which are replicated worldwide. Integrated Water Resources management (IWRM) and the Human Right to Water and Sanitation (HRWS) are two of the main global norms presented as important ideals for good water governance, and as such are seen as contributing to achievement of the Sustainable Development Goals (SDGs). This article engages with this logic. Purpose: The article analyses two global water norms in Central America: the IWRM and HRWS, from their regional and national definitions and implementation in order to respond to the following research question: does the adoption of IWRM and the HRWS in Central American water management represent normative coherence for development or normative hegemony manifested by vertically imposed global water governance norms? Methods and approach: The research examines the definition and implementation of IWRM and the HRWS in the Central American Integration System (SICA) and six member states. It examines regional legal frameworks and national water laws and policies. Data collection included reviews of policy documents, academic studies, and grey literature from regional organizations and fieldwork conducted from 2012 to 2019. Findings: IWRM and HRWS are global water norms that have been institutionalized in Central America through development co‐operation partnerships, especially with European donors. This research shows that SICA member states have not implemented these norms due to the opposition of diverse coalitions of water stakeholders, including agribusiness, economic elites, and indigenous communities. The findings indicate that stakeholder participation and normative legitimacy are the defining characteristics that separate normative coherence for sustainable development from normative hegemony. Policy implications: Despite Central America's legal alignment with the SDGs, significant grassroots opposition to the implementation of global water norms across the region suggests that normative coherence for sustainable development depends on normative alignment and incorporation by states in national legal frameworks but is also conditioned by stakeholder participation. These findings indicate that normative coherence for sustainable development should become more participative in nature in order to promote transformative development as defined by the SDGs. Otherwise, stakeholders may perceive it as normative hegemony.